STEP FORWARD FOR CFD UNCERTAINTY ANALYSIS OF SHIP RESISTANCE BENCHMARK MODEL LHI-007 - Rina, Rina; Purnamasari, Dian; Dwi Yulfani, Rosi; Johar Alif Rahadi, Shinta (Journal of Marine-Earth Science and Technology, 2022)
Computational Fluid Dynamics (CFD) is a tool for solving the basic problems of equations for model flow motion. The CFD application can be used to predict the magnitude of the ship's resistance which is related to the engine power needed to move the ship. Benchmarking is the process of comparing different methods, procedures, and physical models to provide a common basis for the validation of numerical methods. This study simulates the resistance test on the LHI 007 benchmark ship model using FINE™/Marine with speed ranges 1.63 m/s – 2.47 m/s at a temperature of 27°C. The purpose of this research is to complete the simulation approach and numerical uncertainty for the previous study. By adding a time step component to the verification and validation of the uncertainty analysis, the error value gets smaller than the validation value for various speeds 1.63 m/s, 1.8 m/s, 1.91 m/s and 2.02 m/s. It shows that validation was achieved.